Corrosion in concrete structures with permanent deformation in marine environment - Ortega, Nestor Francisco (2017)
Concrete is usually highly alkaline (pH around 12), thus protecting reinforcement against corrosion. The occurrence of oxides is favored when the medium pH surrounding the bar is in values near to 9 or lower. Aggressive substances for reinforcements generally enter concrete through its pore structure, and cracks tend to decrease pH, stimulating corrosion process. There are several causes for cracks, including structure bending caused by loads. This research established the influence of concrete coating cracks, caused by permanent deflection, on the durability of reinforced concrete beams in contact with chloride-containing water (at a similar ratio as seawater), over a five-year period. It analyzes the influence of deflections suffered by the specimens on corrosion potentials and concrete coating cracking. It was established that, from the durability point of view and for structures exposed to marine environment, it would be advisable to set stricter admissible deflection and/or concrete cracking limits than those set by the analyzed standards.